PROSEDUR PEMBAYARAN UTANG KEY OPINION LEADER (KOL) PADA PT FORMASI AGUNG SELARAS - Shafira Audin Azzahra (2022)
Through this final project, the author aims to learn more about the Key Opinion Leader (KOL) debt payment procedure at PT Formasi Agung Selaras and as one of the requirements for graduation from the Diploma Three program for the Accounting Department, Universitas Pembangunan Nasional Veterans Jakarta. PT Formasi Agung Selaras is a company that operates in the entertainment, content, and influencer marketing industries that provides marketing strategy services to promote a product from a brand to the general public carried out by Key Opinion Leaders (KOL) through social media. A procedure is an activity that is carried out in stages and involves several departments to complete an activity or problem. Debt payment procedures are required to settle a debt activity that arises as a result of the purchase of goods or services on credit as was done by PT Formasi Agung Selaras in carrying out the Key Opinion Leader (KOL) debt payment process.